PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR KIMIA SISWA PADA MATERI LARUTAN PENYANGGA DI SMAN 5 KOTA BENGKULU - Rantika Khumairah; Agus Sundaryono; Dewi Handayani (ALOTROP, 2020)
The purposes of this study is to know student learning outcomes of chemistry using flipped classroom learning model and know influence of flipped classroom learning model to on buffer solution. The study was conducted in February-March of 2019 in SMAN 5 Bengkulu City This study is pre-experimental design with one-grup pretes-posttest design. Population of this study is all of XI MIPA’s student which a total of 216 students with sample of this study is XI MIPA 5’s student which a total of 36 students. Technique of sampling in this study is used with purposive sampling technique. Instrument of this study used test of learning outcomes with 20 items pretest and posttest. Analysis of the data used are mean values, normality test, homogeneity test, and t-test to the student learning outcomes. Based on normality test and homogeneity test obtained that pretest and posttest have normal distribution and distributed to homogeneous. Average value of pretest and posttest are 60,1 and 80,0. The result of hypotheses using t-test showed that value of significance is 0.000 < 0.05, so flipped classroom model influenced of significance to student learning outcomes. The result of this study showed that flipped classroom learning model can positive influence to learning outcomes and increased student learning outcomes on buffer solution in XI MIPA 5 SMA N 5 Bengkulu city on academic year of 2018/2019.